Upaya Meningkatkan Prestasi Belajar Siswa Kelas VII-1 MTs Nurhidma Materi Ilmuwan Muslim pada Masa Dinasti Umayyah Dengan Metode Card Sort - Sugiyanto , Sugiyanto; Ma’mun Hanif (Lembaga Pengembangan Kinerja Dosen, 2022)
This study aims to determine student learning outcomes after participating in learning with the Card Sort method in SKI lessons on Muslim Scientists and their role during the Umayyad dynasty. This research is a class action research (PTK), the subject of this research is class VII-1 students of MTs Nurul Hidayah Majalangu Watukumpul District, Kab. Pemalang for the 2020/2021 school year with a total of 33 students. The instruments used in this study were observation, interviews, learning achievement tests, and documentation. The results showed that before the card sort method was applied (pre-cycle activities) student achievement was still relatively low, namely the percentage of students who achieved KKM was 39.39%, after learning using the card sort method the percentage of students could increase, namely achieving KKM in cycle I 72 .73% then becomes 90.45% in cycle II. Overall it can be concluded that the card sort method can improve students' learning achievement (results) in SKI lessons about Muslim Scientists and their role during the Umayyad dynasty.